Storage of serotonin in vivo as a complex with serotonin-binding protein in central and peripheral serotonergic neurons - Gershon, MD (J Neurosci, 1983)
Serotonin-binding protein (SBP) is a soluble protein found in synaptic vesicles of central and peripheral serotonergic neurons. Experiments were undertaken to determine whether serotonin (5-HT) is physiologically stored as a complex with SBP in vivo. [3H]5-HT was used as a probe. Neurons were allowed to specifically take up the labeled amine and attempts were made to recover the in vivo formed [3H]5-HT X SBP complex. Rats were perfused intraventricularly (3 hr) with [3H]5- HT. Strips of rabbit enteric nervous system (ENS) were incubated with [3H]5-HT in the presence of desipramine. The tissues were then homogenized so as to disrupt synaptic vesicles; protein-bound [3H]5-HT was obtained from the 100,000 X g supernatant by filtration on Sephadex G-50 and subjected to sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Studies with [3H]5-HT added just prior to homogenization indicated that the [3H]5-HT X SBP complex had formed intraneuronally, prior to homogenization. The protein X [3H]5-HT complexes from brain and gut migrated on the gels with apparent molecular weights of 45,000 and 56,000, corresponding to those measured by SDS-PAGE for purified SBP; however, the 45-kilodalton (kd) molecule predominated when the SBP complex was formed in vivo, whereas the 56-kd molecule predominated when the SBP X [3H]5-HT complex was formed with extracted SBP. It is possible that the 56-kd SBP is characteristic of the molecule in perikarya or nonterminal axons, whereas the 45-kd molecule is characteristic of terminal varicosities because radioautographic results show that in both the central nervous system and ENS, [3H]5-HT is mostly concentrated in terminals. In any case, newly taken up [3H]5-HT preferentially labels 45-kd SBP. Depletion of endogenous 5-HT by placing animals on a tryptophan-deficient diet increased the amount of exogenous [3H]5-HT bound to SBP in vivo. This suggests that endogenous 5-HT is normally bound to SBP and competes with the [3H]5-HT probe for available binding sites. The binding of 5- HT to SBP within vesicles may be important to reduce the osmotic pressure that would build up in synaptic vesicles if 5-HT were free in solution.